RETRACTED: Agrochemical properties of the soils of intensive apple orchards in Bukhara region - Yunusov R.; Ganiyeva F.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001